Simple is simply not enough—features versus labels of complex financial securities - Martin Hibbeln; Werner Osterkamp (Review of Derivatives Research, 2024)
Abstract We examine how design features and labels of complex financial securities affect pricing and performance. Hence, we utilize the security design features required by the European Union's Securitization Regulation and the optional STS label (“Simple, Transparent, and Standardized”). Based on a unique dataset of European securitizations with 31 million quarterly loan observations, we find that investors hardly consider the features but rely on the existence of the label, although the latter has no performance-increasing effect. Our results reveal that investors neglect a proper risk assessment and misinterpret the easily accessible label as a signal of superior performance.
Additional information: D82;G01;G18;G21
Keywords: 330; Asset-backed securities; EU securitization regulation; Simple; transparent; standardized (STS); Loan performance; Complex securities